Production of deuterons, tritons, 3He nuclei, and their antinuclei in pp collisions at √s=0.9, 2.76, and 7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Beck, Hans; Borissov, Alexander; Danisch, Meike; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; et al. (Physical review, 2018)
Invariant differential yields of deuterons and antideuterons in pp collisions at √s = 0.9, 2.76 and 7 TeV and the yields of tritons, 3He nuclei, and their antinuclei at √s = 7 TeV have been measured with the ALICE detector at the CERN Large Hadron Collider. The measurements cover a wide transverse momentum (pT) range in the rapidity interval |y|<0.5, extending both the energy and the pT reach of previous measurements up to 3 GeV/c for A=2 and 6 GeV/c for A=3. The coalescence parameters of (anti)deuterons and 3¯¯¯¯He nuclei exhibit an increasing trend with pT and are found to be compatible with measurements in pA collisions at low pT and lower energies. The integrated yields decrease by a factor of about 1000 for each increase of the mass number with one (anti)nucleon. Furthermore, the deuteron-to-proton ratio is reported as a function of the average charged particle multiplicity at different center-of-mass energies.
S. Acharya, V. Anguelov, M. Arslandok, H. Bock, A. Borissov, M.C. Danisch, P. Glässel, J. Kim, M.K. Köhler, S. Klewin, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere] (ALICE Collaboration)
Gesehen am 04.07.2019